Experimental and thermodynamic assessment of the Gd-Ti-Zr phase diagram. (June 2018) - Mattern, N.; Han, J.H.; Nowak, R.; Fabrichnaya, O.; Kaban, I.; Shuleshova, O.; Sobczak, N.
Abstract: The phase diagram of the ternary Gd-Ti-Zr system has been investigated. The phase equilibria behave as a pseudo-binary Gd-(Ti, Zr) system with the solid state been characterized by the coexistence of elemental Gd and (Ti, Zr) solid solution phase with low solubility (< 1 at%) of the other elements. A continuous eutectic line connects the eutectic points of the binary Gd-Ti and Gd-Zr terminal systems. The stable miscibility gap of the liquid phase of the Gd-Ti system extends up to 15 at%Zr into the ternary alloy system. The liquidus line and phase sequence were experimentally assessed for Gd20 Ti40 Zr40, Gd40 Ti20 Zr40 and Gd40 Ti50 Zr10 by in situ high energy synchrotron X-ray diffraction at elevated temperatures. Based on the experimental data a thermodynamic description of the ternary Gd-Ti-Zr system is derived. Graphical abstract: fx1 Highlights: The ternary Gd-Ti-Zr phase diagram is presented for the first time. The Gd-Ti-Zr system behaves as a pseudo-binary Gd-(Ti, Zr) system. The miscibility gap of the liquid phase extends up to 15 at% Zr. A consistent thermodynamic description of the Gd-Ti-Zr system is derived.